Captured images: a semiotic analysis of early 20th Century American schools - Caswell, Heather C. (Kansas State University, 2012)
This study investigates visual representation of three perspectives: the context of school, the pedagogy, and the teacher-student relationships when viewing photographs taken during the first half of the 20th Century of American Schools. Grounded in the understanding of visual culture, this image-based study utilized photographs as a rich source of data. The photographs collected for this study were taken between 1900 -1959 in American schools and were categorized by the Library of Congress as still images of classrooms in the United States. The Library of Congress collection was utilized to provide reliable categorized and documented images of schooling. The collection included 1,812 photographs archived in the Library of Congress Prints and Photographs collections specifically labeled as Classrooms United States; the non-digitized Frances Benjamin Johnston Photograph Collection of United States Indian School; and, Look Magazine Teacher Issue Charlotte Brooks negatives collection. A three-layered analysis utilized an initial layer of analysis placing each of the photographs into four predetermined categories: Time Period (1900-1950’s), Urban-Rural, Wealth-Poverty, Active-Passive environment. The placement of each photograph into the above continua provided evidence of the balance of visual elements within the data collection. Seven themes emerged through an open-coding process within the second layer of analysis when each photograph was coded using a specific perspective: context, pedagogy, and teacher-student relationship. As themes were extracted, a third layer of analysis utilized a semiotic approach to identifying over 20 cultural icons representational of schooling within the photograph. Implications for further research are provided.
Keywords: Schooling; Images; Education, General (0515)